Turkish nursing students' knowledge of and attitudes towards patients with HIV/AIDS. Issue 23 (15th October 2013) - Akin, Semiha; Mendi, Basak; Mendi, Onur; Durna, Zehra
Abstract : Aims and objectives: To assess nursing students' knowledge of and attitudes towards such patients and to determine the variables associated with students' knowledge and attitudes towards them. Background: Improving nurses' and nursing students' knowledge and attitudes towards patients with HIV/AIDS is vital for providing quality care for such patients. Design: This descriptive, cross‐sectional study was conducted at three nursing schools located in two different cities in Turkey. The inclusion criteria for the nursing students were as follows: being at least 18 years old; being a first‐, second‐, third‐ or fourth‐year nursing student; and giving consent to participate in the research. Methods: The sample comprised 580 nursing students. The study used three data collection tools: (1) the Student Socio‐Demographic Questionnaire, (2) the HIV/AIDS Knowledge Questionnaire and (3) the HIV/AIDS Attitude Questionnaire. Results: Participants' knowledge was found to be insufficient, particularly with regard to HIV transmission routes. They generally had positive attitudes towards patients with HIV/AIDS. However, they expressed some concerns and were hesitant about working with AIDS and HIV‐positive patients. Conclusions: The current results reveal that nursing students still have misconceptions and a lack of knowledge of HIV/AIDS and that their attitudes need to be improved. Relevance to clinical practice: Improving education programmes about HIV/AIDS and using information sources effectively may contribute to better knowledge and more desirable attitudes towards HIV/AIDS.